2002
DOI: 10.1038/sj.npp.1300111
|View full text |Cite
|
Sign up to set email alerts
|

The Phospholipase C-IP3 Pathway is Involved in Muscarinic Antinociception

Abstract: The cellular events involved in muscarinic analgesia were investigated in the mouse hot-plate test. Intracerebroventricular (i.c.v.) pretreatment with antisense oligonucleotides (aODNs) against the a subunit of G q and G 11 proteins prevented the analgesia induced by physostigmine and oxotremorine. Furthermore, administration of the phospholipase C (PLC) inhibitor U-73122, as well as the injection of an aODN complementary to the sequence of PLCb 1 , antagonized the increase of the pain threshold induced by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…The involvement of InsP 3 R in the mechanism of analgesic action of cholinomimetics has already been observed [9]. Since both receptor subtypes are involved in intracellular calcium mobilization, in the present study the role played by RyRs in muscarinic antinociception was investigated.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The involvement of InsP 3 R in the mechanism of analgesic action of cholinomimetics has already been observed [9]. Since both receptor subtypes are involved in intracellular calcium mobilization, in the present study the role played by RyRs in muscarinic antinociception was investigated.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that muscarinic antinociception requires the activation of the PLC-InsP 3 pathway. In particular, pretreatment with compounds that inhibit the increase of intracellular Ca 2+ levels through a blockade of InsP 3 R-mediated pathway prevented muscarinic antinociception in mice [9]. However, it should also be taken into account the important role-played by RyRs in the modulation of the intracellular calcium levels.…”
Section: Introductionmentioning
confidence: 99%
“…or calphostin C administered 3 h after NO donors and protein expression detected 4 or 6 h after GNT/ SNP. Doses and administration schedules were chosen on the basis of time-course and dose-response curves performed in our laboratory (Galeotti et al 2003).…”
Section: Western Blotting Experimentsmentioning
confidence: 99%
“…administration of heparin, a potent InsP 3 -receptor antagonist (Jonas et al, 1997), produced a dose-dependent hyperalgesic effect indicating the importance of InsP 3 R in the modulation of pain perception. This hypothesis is supported by data indicating that the blockade of InsP 3 R by heparin, as well as the inhibition of InsP 3 production by LiCl, prevented the analgesic effect of cholinomimetic drugs (Galeotti et al, 2003) and delta opioid agonists (Narita et al, 2000). Heparin must be injected into cells or perfused onto permeabilized cells because of its high molecular weight (12 000-13 000 Da) and lack of membrane permeability.…”
Section: Discussionmentioning
confidence: 85%
“…Antinociception produced by cholinomimetic drugs is prevented by i.c.v. pretreatment with compounds that inhibit the increase of intracellular Ca 2+ levels (Galeotti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%